Novel missense variants in brain morphogenic genes associated with depression and schizophrenia - Karagyaur, Maxim; Primak, Alexandra; Bozov, Kirill; Sheleg, Dmitriy; Arbatsky, Mikhail; Dzhauari, Stalik; Illarionova, Maria; Semina, Ekaterina; Samokhodskaya, Larisa; Klimovich, Polina; Velichko, Arkadiy; Drach, Mikhail; et al. (Frontiers in Psychiatry, 2024)
Introduction Impaired function of brain morphogenic genes is considered one of the predisposing factors for the manifestation of psychiatric and cognitive disorders, such as paranoid schizophrenia (SCZ) and major depressive disorder (MDD). Identification of such genes (genes of neurotrophic factors and guidance molecules among them) and their deleterious genetic variants serves as a key to diagnosis, prevention, and possibly treatment of such disorders. In this study, we have examined the prevalence of genomic variants in brain morphogenic genes in individuals with SCZ and MDD within a Russian population. Methods We have performed whole-exome sequencing of 21 DNA samples: 11 from individuals with SCZ and 10 with MDD, followed by ARMS (Amplification-Refractory Mutation System) based screening of detected single nucleotide variants (SNVs) in larger groups: 102 for individuals with SCZ, 79 for those with MDD and 103 for healthy donors. Results Whole-exome sequencing has revealed 226 missense mutations in 79 genes (out of 140 studied), some of which occur in patients with psychiatric disorders significantly more frequently than in healthy donors. We have identified previously undescribed genomic variants in brain morphogenic genes: CDH2 (rs1944294-T and rs17445840-T), DCHS2 (rs11935573-G and rs12500437-G/T) and CDH23 (rs1227051-G/A), significantly associated with the incidence of SCZ and MDD in the Russian population. For some SNVs (rs6265-T, rs1944294-T, rs11935573-G, rs4760-G) sex-biased differences in their prevalence between SCZ/MDD patients and healthy donors was detected. Discussion However, the functional significance of the SNVs identified has still to be confirmed in cellular and animal models. Once it is fulfilled, these SNVs have the potential to complement the diagnostic toolbox for assessing susceptibility to mental disorders. The data obtained indirectly confirm the importance of adequate brain structure formation for its correct functioning and preservation of mental health.